The development of a measure of orthographic knowledge in the Arabic language: A psychometric evaluation. (23rd May 2021) - Tibi, Sana; Fitton, Lisa; McIlraith, Autumn L.
Abstract: Although Arabic is an official language in 27 countries, standardized measures to assess Arabic literacy are scarce. The purpose of this research was to examine the item functioning of an assessment of Arabic orthographic knowledge. Sixty novel items were piloted with 201 third grade Arabic-speaking students. Participants were asked to identify the correctly spelled word from a pair of two words. Although the assessment was designed to be unidimensional, competing models were tested to determine whether item performance was attributable to multidimensionality. No multidimensional structure fit the data significantly better than the unidimensional model. The 60 original items were evaluated through item fit statistics and comparing performance against theoretical expectations. Twenty-eight items were identified as functioning poorly and were iteratively removed from the scale, resulting in a 32-item set. A value of 0.987 was obtained for McDonald's coefficient ω from this final scale. Participants' scores on the measure correlated with an external word reading accuracy measure at 0.79 ( p < .001), suggesting that the tool may measure skills important to word reading in Arabic. The task is simple to score and can discriminate among children with below-average orthographic knowledge. This work provides a foundation to develop Arabic literacy assessments.